2020
DOI: 10.15252/msb.20209610
|View full text |Cite
|
Sign up to set email alerts
|

The protein expression profile of ACE2 in human tissues

Abstract: The novel SARS-coronavirus 2 (SARS-CoV-2) poses a global challenge on healthcare and society. For understanding the susceptibility for SARS-CoV-2 infection, the cell type-specific expression of the host cell surface receptor is necessary. The key protein suggested to be involved in host cell entry is angiotensin I converting enzyme 2 (ACE2). Here, we report the expression pattern of ACE2 across > 150 different cell types corresponding to all major human tissues and organs based on stringent immunohistochemical… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

49
671
4
16

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 861 publications
(740 citation statements)
references
References 67 publications
49
671
4
16
Order By: Relevance
“…1D) to understand how air-liquid interface and co-culture may alter the expression of SARS-CoV-2 entry factors. In epithelial cells, ACE2 expression was low both in monoculture ( Fig S1A) and on-chip ( Fig 1D) consistent with transcriptomic 16,20 and proteomic analyses 21 of human tissue. Expression on-chip was five-fold lower than monoculture (Fig.…”
Section: Sars-cov-2 Infection Alters Relative Expression Of Viral Entsupporting
confidence: 75%
“…1D) to understand how air-liquid interface and co-culture may alter the expression of SARS-CoV-2 entry factors. In epithelial cells, ACE2 expression was low both in monoculture ( Fig S1A) and on-chip ( Fig 1D) consistent with transcriptomic 16,20 and proteomic analyses 21 of human tissue. Expression on-chip was five-fold lower than monoculture (Fig.…”
Section: Sars-cov-2 Infection Alters Relative Expression Of Viral Entsupporting
confidence: 75%
“…Our data underscore the possibility that the variation in the viral quasispecies that we see is not generated in the naso-or oropharynx, but rather more distally in the respiratory tract (lungs) or even in other tissues such as the gut. Reports on the comparative expression of the virus' cellular receptor ACE2 support the idea that those other tissues might be relevant sources of viral replication and, consequently, sites where diversity emerges [21,22].…”
Section: Discussionmentioning
confidence: 95%
“…While the majority of hospitalized COVID-19 patients present with compromised airway function, a wide variety of effects on other organs have been noted. The primary SARS-CoV-2 receptor, angiotensin converting enzyme 2 (ACE2 59 ), is expressed in a wide variety of cell types 60 , including cardiomyocytes, cardiac pericytes, endothelial cells, fibroblasts, hepatocytes and multiple cell types in the kidney 61 , and kidney impairment 62,63 , cardiac injury 64 and liver dysfunction 65,66 are commonly observed in COVID-19 critical care patients. While the virus-related cytokine storm has been linked to organ damage 67 , a recent report also indicated that SARS-CoV-2 virus RNA was found in autopsied lung, pharynx, heart, liver, kidney, and brain 68 .…”
Section: Discussionmentioning
confidence: 99%